Operating Room Set Up in Endoscopic Skull Base Surgery - Alessandra Alfieri; Paola Flavia Schettino; Luisa Scognamiglio; Nunzio Guarino; Raffaele Schettino; Giovanni Schettino (Medical Science: Trends and Innovations Vol. 11, 2025)
Since the introduction of endoscopic endonasal surgery for skull base pathologies in the 1990s, increasing experience with this technique has led to many progressive changes in patient positioning, technique, and set-up in the operating room. In addition, new surgical instruments have been developed for endoscopic endonasal skull base surgery. The experience in assessing the operating room and surgical instruments in the last 267 endoscopic endonasal skull base procedures was reported. The endoscopic technique has broadened the indications for endonasal skull base pathology. This technique always requires a previous cadaveric study in the laboratory in order to have a precise knowledge of the anatomy from an endonasal point of view. Since the first procedures, dealing with intraoperative hemorrhage was learned. The 3D technique has been used in the last 57 procedures and has improved the overall depth perception, with a true microscope-like view and better control of the lesion and neurovascular structures.